Sex differences between serum uric acid levels and cardiovascular outcomes in patients with coronary artery disease after stent implantation - Yuan, Song Lin; Kim, Moo Hyun; Lee, Kwang Min; Jin, Xuan; Song, Zhao Yan; Park, Jong-Sung; Cho, Young-Rak; Lim, Kyunghee; Yun, Sung-Cheol (Frontiers in Cardiovascular Medicine, 2023)
Background The relationship between elevated serum uric acid (SUA) levels and cardiovascular outcomes after stent implantation remains uncertain. This study sought to evaluate the impact of SUA on 12-month cardiovascular outcomes after stent implantation. Methods We performed a retrospective study of patients who successfully underwent stent implantation and enrolled 3,222 patients with coronary artery disease (CAD) from a single center. SUA levels were measured before stent implantation. The patients were divided into six groups (<4, 4–4.9, 5–5.9, 6–6.9, 7–7.9 and ≥ 8 mg/dL) at SUA intervals of 1.0 mg/dL. The incidence of cardiovascular outcomes in the six groups was monitored for 1 year after stent implantation and the hazard ratios were estimated. Hazard ratios (HRs) and 95% confidence intervals (95% CIs) for cardiovascular outcomes were estimated using a Cox proportional hazard regression analysis. The primary endpoint was all-cause death. The secondary endpoint was a composite of all-cause death, myocardial infarction, target vessel revascularization, stent thrombosis and stroke. The follow-up duration was 12 months. Results Over the 12-month follow-up period, there were 101 all-cause deaths and 218 MACCE. After adjustment for several parameters, the group with SUA levels of more than or equal to 8 mg/dL had significantly higher hazard ratios in the incidence of all-cause death or MACCE. The group with <4.0 mg/dL had significantly higher hazard ratios in all-cause death only in male patients. In contrast, there were no significant differences observed for cardiovascular outcomes in female patients. Conclusions Our study identified a U-shaped association between SUA levels and cardiovascular outcomes during 12-month follow-up for males, but not for females. Further studies are warranted to clarify the sex differences between SUA levels and clinical outcomes.